Improving Students' Faith and Taqwa by Memorizing the Qur'an Using the Murojaah Method in Kindergarten B Class - Destiana, Evie; Aviola, Adelia Anandra; Taufiq, Salwa; Rahayu, Yovana Enanda (Procedia of Social Sciences and Humanities, 2024)
The Quran is the holy book of Muslims, the Quran memorization program is one of the breakthrough programs used by educators referring to the six scopes of early childhood development, one of which is the moral and religious aspects. This research uses qualitative research. This study focuses on strengthening the ability to memorize the Qur'an through habituation of muroja'ah students at Tk Aisyiyah 1 Candi Memorizing the Qur'an using the murojaah method at Tk Aisyiyah 1 Candi aims to produce a Quranic generation. Therefore, memorizing the Qur'an is used as one of the superior programs that is adjusted to the vision and mission of Tk Aisyiyah 1 Candi. Why does Tk Aisyiyah use the murojaah method because it is one of the determinants of success in memorization. The class teacher applies the murojaah method by repeating the previous verse and continuing the next verse by reading Surah An-Naba verses 10-15 and repeating verses 5-10, after listening students are asked to repeat the reading one by one Implementation of the muraja'ah method by using the muraja'ah memorization deposit program to the teacher to make it easier for students to maintain memorization of the Qur'an so that it is not easy for students to forget it. The implementation of this muraja'ah method can be done anytime and anywhere, because the process of implementing this muraja'ah method is not bound by time as long as there is a will.